2023
DOI: 10.1021/acsomega.2c06634
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin and Empagliflozin Inhibit Microtubule Affinity Regulatory Kinase 4: Repurposing Anti-Diabetic Drugs in Neurodegenerative Disorders Using In Silico and In Vitro Approaches

Abstract: Type 2 diabetes mellitus (T2DM) and Alzheimer's disease (AD) are significant public health burdens. Many studies have revealed the possibility of common pathophysiology between T2DM and AD. Thus, in recent years, studies deciphering the action mechanism of anti-diabetic drugs with their future use in AD and related pathologies are on high demand. Drug repurposing is a safe and effective approach owing to its low cost and time-saving attributes. Microtubule affinity regulating kinase 4 (MARK4) is a druggable ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…The Marks contain four members of Mark1-4, which are located on human chromosomes 1, 11, 14 and 19, respectively, and play distinct physiological regulatory [ 36 ]. Numerous studies have shown that Mark4 is closely associated with the occurrence of diverse diseases, including cancer [ 13 ], Alzheimer’s disease [ 37 ], and cardiovascular disease [ 38 , 39 ]. In the current study, we found that the expression levels of all Marks except Mark3 was increased in high phosphorus-induced VSMCs, while the elevation of Mark4 was the most pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…The Marks contain four members of Mark1-4, which are located on human chromosomes 1, 11, 14 and 19, respectively, and play distinct physiological regulatory [ 36 ]. Numerous studies have shown that Mark4 is closely associated with the occurrence of diverse diseases, including cancer [ 13 ], Alzheimer’s disease [ 37 ], and cardiovascular disease [ 38 , 39 ]. In the current study, we found that the expression levels of all Marks except Mark3 was increased in high phosphorus-induced VSMCs, while the elevation of Mark4 was the most pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Wykazano, że zahamowanie nadmiernej aktywacja kinazy MARK4 może zmniejszyć rozwój choroby Alzheimera oraz zahamować rozwój nowotworów. [26] Aktualnie oczekujemy na wyniki pilotażowego randomizowanego badania kontrolowanego (NCT03801642) przeprowadzanego przez University of Kansas Alzheimer's Disease Center oceniającego wpływ dapagliflozyny na pacjentów dorosłych z łagodną lub umiarkowaną chorobą Alzheimera. [27]…”
Section: Figura 4 Mechanizmy Neuroprotekcyjne Inhibitorów Sglt2 Odgry...unclassified
“…In addition, a wealth of evidence indicates a strong participation of SGLT2i in improving cognitive functions, by inhibiting AChE activity and increasing the acetylcholine levels [21][22][23][24]. Furthermore, these compounds improve peripheral insulin sensitivity, as well as brain signaling, which is impaired in the AD pathogenesis [25].…”
Section: Introductionmentioning
confidence: 99%